Gray images of the linear codes and their dual codes over F4+uF 4 - Xiu-sheng LIU; Hua-lu LIU (Tongxin xuebao)
The linear codes over ring F4＋uF4 and field F4 were studied.By using the Gray weight wG ,the Gray distance dG of codes C over F4＋uF4,and the Gray map ψ from (F4＋uF4)n to <msubsup> F 4 2n </msubsup> ,the Gray image ψ(C)of linear codes C over F4＋uF4 were linear codes over F 4 as well,d H(ψ(C))＝d G(C),and the proposition that linear codes ψ(C )⊥ were the dual codes of ψ(C) were showed.Furthermore,the Gray image ψ(C)of cyclic codes C over F4＋uF4 were the 2-quasi cyclic codes over F4.